Degradation of metronidazole simulated water by nanosecond pulsed DBD plasma. Issue 1 (March 2021) - Fan, Yangyang; Cheng, Jiushan; Chen, Qiang
Abstract: In this work, nanosecond pulsed dielectric barrier discharge (nsp-DBD) plasma was used to degrade metronidazole simulated water under Air gas. The effects of initial concentrations, pulse peak voltages and air flow rates on metronidazole degradation were investigated, respectively. The role of hydroxyl radical in the metronidazole degradation was emphasized. The variations of solution pH value and conductivity during the discharge process were measured. Experimental results show that nsp-DBD plasma can effectively degrade metronidazole simulated water. When the initial concentration was 100 mg/L, the pluse peak voltage was 15 kV, and the air flow rate was 3 L/min, the degradation efficiency and energy yield of metronidazole were 92% and 1.83g/kWh, respectively, after 25 min treatment. The mineralization rate reached 39% after 60 min of treatment. The scavenger experiment proved that the hydroxyl radical was the main active species in metronidazole degradation. The solution pH was significantly reduced, and the conductivity was greatly increased after plasma treatment, which were corresponded to the formation of NO3 −, NO2 − and intermediate products in the degradation process.